Dark Humor in the Poetry of Sherman Alexie and Ahmed Matar: A Comparative Study - Mustafa Amjed Jasim Al-Hemeedawi; Shahad Ammar Adul Hadi (RIRAI Publisher, 2023)
Dark humor is a form of comedy that explores taboo topics such as death, disease, and tragedy. While it is often controversial and can be offensive to some, it is also a means of coping with difficult or uncomfortable topics and offering a fresh perspective on societal norms. Just as stated by Merriam-Webster’s Encyclopedia of Literature, dark humor or black humor is a kind of humor that is marked by the use of morbid, ironic, or grotesquely comic episodes that ridicule human folly. However, this paper examines the concept of dark humor by tackling some of the significant poems of the English poet “Sherman Alexie” and the Iraqi poet “Ahmed Matar.” Those two poets discuss subjects and problems of real-life experiences. The purpose of this research is to shed light on Native Americans' daily lives on reservations and demonstrate their pain as well as the poet’s personal experience there, which is discussed by Sherman Alexie in his poems, “Futures”, “Traveling”, “Translated from the American”, “Giving Blood”, “War all the time”, “Reservation cap driver”, “The mice war”. While the Iraqi poet tended to criticize Arab rules, the lack of freedom they force, their use of torture, the government, and their persuasion of authority at all costs. Here are some of his notable poems that this research are going to explain and make critique in details. “They put a watchdog on my mouth